Airway management with novel intubating laryngeal tubes has no influence on cerebral oxygenation in cardiac surgery patients: A prospective observational study - Kriege, Marc; Rissel, René; Heid, Florian; Ott, Thomas; Beyrouti, Hazem El; Hotz, Eric (Frontiers in Anesthesiology, 2022)
Background A laryngeal tube is often used as an alternative to intubation with direct laryngoscopy during cardiopulmonary resuscitation. However, in a study with piglets undergoing simulated cardiac arrest, reduced carotid artery blood flow was associated with the insertion of different supraglottic airway devices, such as a laryngeal tube. Limited by its construction, secondary tracheal intubation through a laryngeal tube was difficult or impossible in contrast to a second generation laryngeal mask. The new disposable intubating laryngeal tube with suction (iLTS-D®) seems to facilitate tracheal intubation. We hypothesized that iLTS-D, when inflated to the recommended air volume, does not reduce cerebral oxygenation in patients with cardiovascular diseases undergoing elective cardiac surgery. Methods This single-center prospective, controlled observational study was approved by the local ethics committee (Ethical Committee No. 2018-13716). Forty adult patients undergoing elective cardiac surgery requiring tracheal intubation were included in this study. The exclusion criteria were age <18 years and a high risk of aspiration, inability to consent, height <155 cm, or pregnancy. Prior to insufflation and deflation of the cuffs, we performed cerebral oximetry via near-infrared spectroscopy. The primary outcome was a significant reduction in NIRS in the context of the preinduction baseline value after inflation of the cuffs with the recommended air volume, defined as a ≥25% decrease from baseline or an absolute value ≤ 50%. The secondary endpoints were differences in time points, insertion success rates, and complications. Results There was no significant reduction in cerebral oximetry after inflation with the recommended cuff volume and an initially measured cuff pressure of >120 cmH2O. Overall, tracheal intubation was achieved in a median of 20 s [interquartile range 15-23 s] and enabled sufficient ventilation and tracheal intubation through the iLTS-D in all patients. Traces of blood on the cuffs (after removing the iLTS-D) and a sore throat (evaluated 2 h after removing the tracheal tube) were observed in one patient. Conclusion Our results showed no association between the insertion of the iLTS-D and reduced cerebral oxygenation in patients undergoing elective cardiac surgery. Trial registration ClinicalTrials.gov, NCT03942809.